New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae) - Monné, Miguel A.; Nascimento, Francisco E. De L.; Monné, Marcela L.; Santos-Silva, Antonio (Zootaxa, 2019)
Notes and new country records are provided for Leptostylus retrorsus Bates, 1885, and Lagocheirus araneiformis flavolineatus Aurivillius, 1921. The male of Trichalcidion penicillum Monné & Delfino, 1981 is described for the first time, and a new country record is provided. One new genus and four new species are described: Vitacinis luziae from Colombia (new genus); Nealcidion antonkozlovi from Colombia; Onalcidion antonkozlovi from Colombia; and Leptocometes antonkozlovi from Colombia. Hemilocallia grishami Ramírez Hernández et al., 2019 is synonymized with Glenea (Glenea) fasciata (Fabricius, 1781) [Hemilocallia = Glenea (Glenea); H. grishami = G. (G.) fasciata].